2019
DOI: 10.1016/j.hpb.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and evaluation of the severity of acute respiratory distress syndrome following severe acute pancreatitis using an artificial neural network algorithm model

Abstract: Background: To predict the risk and severity of acute respiratory distress syndrome (ARDS) following severe acute pancreatitis (SAP) by artificial neural networks (ANNs) model. Methods: ANNs model was constructed by clinical data of 217 SAP patients. The model was first trained on 152 randomly chosen patients, validated and tested on the 33 patients and 32 patients respectively. Statistical analysis was used to assess the value of it. Results:The training, validation, and test set were not significantly differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 31 publications
1
45
0
3
Order By: Relevance
“…A systematic review of neural network‐based methods noted that these methods have a sensitivity of 0.89 and specificity of 0.96 six hours after admission when compared with APACHE II (cutoff score ≥ 8) with 0.80 and 0.85, respectively 8 . Several other studies using AI‐based methods reported similar results 9,11–15 . AI‐based methods could also identify specific complications of AP such as porto‐venous thrombosis with an accuracy of 83% 16 and intra‐abdominal infections with a receiver operating characteristic curve of 0.923 [0.883–0.952] 17 …”
Section: Artificial Intelligence Applications In Pancreatitismentioning
confidence: 73%
See 1 more Smart Citation
“…A systematic review of neural network‐based methods noted that these methods have a sensitivity of 0.89 and specificity of 0.96 six hours after admission when compared with APACHE II (cutoff score ≥ 8) with 0.80 and 0.85, respectively 8 . Several other studies using AI‐based methods reported similar results 9,11–15 . AI‐based methods could also identify specific complications of AP such as porto‐venous thrombosis with an accuracy of 83% 16 and intra‐abdominal infections with a receiver operating characteristic curve of 0.923 [0.883–0.952] 17 …”
Section: Artificial Intelligence Applications In Pancreatitismentioning
confidence: 73%
“…8 Several other studies using AI-based methods reported similar results. 9,[11][12][13][14][15] AI-based methods could also identify specific complications of AP such as porto-venous thrombosis with an accuracy of 83% 16 and intra-abdominal infections with a receiver operating characteristic curve of 0.923 [0.883-0.952]. 17 One of the earliest applications of AI methods in pancreatobiliary endoscopy is from 1998 where Yeaton et al used decision trees on image variables generated from brush cytology obtained during endoscopic retrograde cholangiopancreatography (ERCP) to distinguish between chronic pancreatitis and pancreatic adenocarcinoma (PDAC) with a sensitivity of 91% and specificity of 87%.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies aimed to predict complications by using an ANN and compared it to logistic regression (LR) modeling. The results showed that the ANN significantly outperformed the LR modeling in predicting the occurrence of several complications during the course of the disease in all three studies 17–19 . Two studies reported ANNs that predict multi‐organ failure (MOF) in AP patients based on clinical and laboratory findings.…”
Section: Pancreatitismentioning
confidence: 97%
“…Several studies report ANNs that predict complications and mortality in patients with AP with high accuracy, ranging from 83.0% to 97.5% 17–23 . Three studies aimed to predict complications by using an ANN and compared it to logistic regression (LR) modeling.…”
Section: Pancreatitismentioning
confidence: 99%
“…In several previous papers, the discriminatory power of logistic regression (LR) and ANN models was compared. [9][10][11] Both models performed equally well in most cases, whereas the more flexible ANN model generally outperforming LR model in the remaining cases. Among the published prediction models for LN metastasis, there are already three LR-based nomograms.…”
Section: Introductionmentioning
confidence: 94%